Answer:
Review both cases and pick the most appropriate answer
Explanation:
First case where it's 9(x^2):
9x^2 + x = 3^4
9x^2 + x = 81
9x^2 + x - 81 = 0
x = b±√(b²-4ac) / 2a
x = 1±√(1²-4(9)(-81)) / 2(9)
x = 1±√(1+2916) / 18
x = 1±√(2917) / 18
x = 1+√(2917) / 18
x = 1-√(2917) / 18
Second case where it's (9x)^2:
(9x)^2 + x = 3^4
(9x)^2 + x = 81
81x^2 + x = 81
81x^2 + x - 81 = 0
x = b±√(b²-4ac) / 2a
x = 1±√(1²-4(81)(-81)) / 2(81)
x = 1±√(1+26244) / 162
x = 1±√(26245) / 162
x = 1+√(26245) / 162
x = 1-√(26245) / 162